DNA barcodes highlight genetic diversity patterns in rodents from lowland desert and Andean areas in Argentina - Ojeda, Agustina Alejandra (2022)
Fil: Ojeda, Agustina Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Argentino de Investigaciones de las Zonas Áridas (Mendoza); Argentina.